2012
DOI: 10.4238/2012.september.12.9
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of 22 polymorphic microsatellite markers for the balloon flower Platycodon grandiflorum (Campanulaceae)

Abstract: ABSTRACT. The balloon flower (Platycodon grandiflorum A. DC.) is a perennial flowering plant of the Campanulaceae family; it is the only member of the genus Platycodon. Information on the genetic diversity of balloon flower populations is of great importance for the conservation and germplasm utilization of this flowering plant. Twenty-two polymorphic microsatellite loci were developed and characterized with eight balloon flower accessions collected from South Korea and China. Eighty-one alleles were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Its roots Platycodi radix are commonly known as doraji in South Korea, jiegeng in China, and kikyo in Japan [ 5 ]. They have been traditionally used as a remedy for cough, cod, bronchitis, asthma, and sore throat [ 6 ]. Previous in vitro and in vivo (animal) studies have shown that Platycodi radix can reduce the elevation of blood TG levels in high-fat diet-fed mice due to inhibition of intestinal absorption of dietary fat [ 7 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its roots Platycodi radix are commonly known as doraji in South Korea, jiegeng in China, and kikyo in Japan [ 5 ]. They have been traditionally used as a remedy for cough, cod, bronchitis, asthma, and sore throat [ 6 ]. Previous in vitro and in vivo (animal) studies have shown that Platycodi radix can reduce the elevation of blood TG levels in high-fat diet-fed mice due to inhibition of intestinal absorption of dietary fat [ 7 8 ].…”
Section: Introductionmentioning
confidence: 99%